Early Prognostication after Traumatic Brain Injury: Specific Validation of the IMPACT Prognostic Calculator in a Level 1 Trauma Center - Jung, Anna; Arlt, Felix; Rosolowski, Maciej; Meixensberger, Jürgen (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
The present study evaluated the usefulness of the IMPACT prognostic calculator (IPC) for patients receiving acute neurointensive care at a level 1 trauma center in Germany. A total of 139 patients with traumatic brain injury (TBI) were assessed. One day after trauma, the extended model of the IPC was found to provide the most valid prediction of 6-month mortality/unfavorable outcome. Different time frames within the first day could be determined by analyzing mild, moderate, and severe TBI cohorts. The CORE + CT model at time frame Z2 (<6 h from the point of first documentation) for mild TBI exhibited the highest values in the receiver operating characteristic (ROC) analysis (area under the curve [AUC], 0.9; sensitivity, 1; specificity, 0.7). For patients with moderate head injury at time frame Z2/3 (<6–12 h from point of first documentation), the extended model fit best. For patients with severe TBI, the extended model at time frame Z6 (48–72 h from point of first documentation) best predicted 6-month mortality and unfavorable outcome (ROC analysis: AUC, 0.542/0.445; sensitivity, 0.167/0.364; specificity, 0.575/0.444). Center-specific validation demonstrated the validity of the IPC in the early phase after TBI. These findings support the usefulness of the IPC for predicting the prognosis of patients with TBI. However, further prospective validation using a larger TBI cohort is needed.
Keywords: prognostication; traumatic brain injury; impact prognosis calculator